Enhancement of the Carbothermal Reduction of Hafnium Oxide by Silicon1 . Issue 1 (16th September 2016) - Weisenseel, Bastian; Harris, Joe; Stumpf, Martin; Wolf, Stephan E.; Fey, Tobias; Greil, Peter
Abstract : Mixtures of hafnia and carbon powders, containing 0.0–10 mol% of silicon, are heated and analyzed by XRD, SEM, TEM, and DTA. Furthermore, hafnia and carbon pellets, with varying degrees of silicon content, are investigated to determine the nature of the silicon influence on the reaction. The addition of up to 5.0 mol% silicon increases the yield of carbide by 400%. TEM reveal that silicon causes the formation of an amorphous layer on the hafnia particles, on which nucleation of the carbide phase take place. Taking into account that the carbide formation in Si‐free samples is only observed on the carbon surfaces, the authors conclude that the silicon‐induced layer on the hafnia surfaces increases the accessible area for carbide formation and consequently the reaction rate. Abstract : A method to significantly increase the carbothermal reduction of HfO2 by the addition of elemental silicon is demonstrated. The carbide yield can be increased by 400%. The silicon addition induces the formation of an amorphous layer on hafnium oxide particles, which increases the accessible surface area for carbide nucleation.